The effects of gradual release of assistance instruction on students’ heuristics, confidence, and attitude toward independent problem-solving - Cerveza, Ryan L.; Lapinid, Minie Rose C. (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The 'Gradual Release of Assistance (GRA) instruction' was implemented among pre-service teachers in a problem-solving course designed to reduce students' resistance to independent problem-solving. This approach aimed to enhance students' heuristic skills, confidence, and attitudes toward problem-solving. The GRA instruction encompassed activities with progressively decreasing levels of instructional support across three stages: the maximum assistance stage, the medium assistance stage, and the independent problem-solving stage. Utilizing an embedded multiple-case design and a simple time-series analysis of six individual cases, this research explored how pre-service teachers applied heuristics and their confidence and attitudes toward problem-solving. The study revealed improvements in heuristic application among cases with high and medium mathematical abilities, as well as increased confidence and positive attitudes toward problem-solving within this cohort. However, there were no notable improvements in using different heuristics among cases with low mathematical ability. The findings discussed the observed changes and consistencies, offering plausible explanations that underscore the significance of GRA instruction in alleviating students' reluctance to engage in independent problem-solving.